The Adjuvants Polyphosphazene (PCEP) and a Combination of Curdlan Plus Leptin Promote a Th17-Type Immune Response to an Intramuscular Vaccine in Mice - Alyssa Chaffey; Glenn Hamonic; Dylan Chand; George K. Mutwiri; Heather L. Wilson (Vaccines, 2021)
Our aim was to determine whether polyphosphazene (PCEP), Curdlan (β-glucan, a dectin-1 agonist), and Leptin could act as adjuvants to promote a Th17-type adaptive immune response in mice. Mice were vaccinated via the intramuscular route then boosted three weeks later with Ovalbumin plus: PCEP, Leptin, Curdlan, PCEP+Curdlan, Curdlan+Leptin, or saline. Mice vaccinated with OVA+PCEP and OVA+Curdlan+Leptin showed significantly higher frequency of antigen-specific CD4+ T cells secreting IL-17 relative to OVA-vaccinated mice. No formulation increased the frequency of CD4+ T cells secreting IL-4 or IFNγ. Since activation of innate immunity precedes the development of adaptive immunity, we wished to establish whether induction of Th17-type immunity could be predicted from in vitro experiments and/or from the local cytokine environment after immunization with adjuvants alone. Elevated IL-6 and TGFβ with reduced secretion of IL-12 is a cytokine milieu known to promote differentiation of Th17-type immunity. We injected the immunostimulants or saline buffer into murine thigh muscles and measured acute local cytokine production. PCEP induced significant production of IL-6 and reduced IL-12 production in muscle but it did not lead to elevated TGFβ production. Curdlan+Leptin injected into muscle induced significant production of TGFβ and IL-17 but not IL-6 or IL-12. We also stimulated splenocytes with media or PCEP, Leptin, Curdlan, PCEP+Curdlan, Curdlan+Leptin, PCEP+Leptin, and PCEP+Curdlan+Leptin and measured cytokine production. PCEP stimulation of splenocytes failed to induce significant production of IL-6, IL-12, TGFβ, or IL-17 and therefore ex vivo splenocyte stimulation failed to predict the increased frequency of Th17-type T cells in response to the vaccine. Curdlan-stimulated splenocytes produced Th1-type, inducing cytokine, IL-12. Curdlan+/-PCEP stimulated TGF-β production and Curdlan+Leptin+/- PCEP induced secretion of IL-17. We conclude that PCEP as well as Curdlan+Leptin are Th17-type vaccine adjuvants in mice but that cytokines produced in response to these adjuvants in muscle after injection or in ex vivo cultured splenocytes did not predict their role as a Th17-type adjuvant. Together, these data suggest that the cytokine environments induced by these immunostimulants did not predict induction of an antigen-specific Th17-type adaptive immune response. This is the first report of these adjuvants inducing a Th17-type adaptive immune response.